DISOLUSI MIKROENKAPSULASI KURKUMIN TERSALUT GEL KITOSAN-ALGINAT-GLUTARALDEHIDA - Herdini, Herdini; Darusman, Latifah K; Sugita, Purwantiningsih (UI Scholars Hub, 2010)
Dissolution of Curcumin Microencapsulation Coated by Chitosan-Alginate-Glutaraldehide. In vitro dissolution of curcumin coated by chitosan-alginate gel in its optimum condition was studied. The maceration process using 17.08% ethanol yields and the content of the curcumin in the extract detected by visible spectrophotometry λ 430 nm is found to be 10.30 %. Its optimum condition was obtained using response surface method at concentrations ratio of alginate 0.62% (b/v) and glutaraldehide 4.63% (v/v) , respectively, where the chitosan concentration was fixed (1.75% [b/v]). The dissolution assay was done at 37 o C, at 100 rpm of stirring rate in 8 hours. Aliquots were taken at 15, 30, 45, 60, 90, 120, 150, 180, 240, 300, 360, 420, 480 minutes. Absorbance of the Aliquots was measured at λ 430 nm. The curcumin released has the best linear correlation to the first order reaction with released constant, k = 2.24 10-3 minute-1 while it’s half live is t1/2 = 5.16 hours. Release curcumin was determined mainly by diffusion mechanism. Compared to the result based on Fick model, the one of Higuchi model is better in agreement in reproducing the released data.